High prevalence of extended-spectrum ß-lactamase producing enterobacteriaceae among clinical isolates in Burkina Faso - Ouedraogo, Abdoul-Salam; Sanou, Mahamadou; Kissou, Aimée; Sanou, Soufiane; Solaré, Hermann; Kaboré, Firmin; Poda, Armel; Aberkane, Salim; Bouzinbi, Nicolas; Sano, Idrissa; Nacro, Boubacar; Sangaré, Lassana; et al. (BMC infectious diseases, 2016)
Nothing is known about the epidemiology and resistance mechanisms of extended-spectrum ß-lactamase-producing Enterobacteriaceae (ESBL-PE) in Burkina Faso. The objective of this study was to determine ESBL-PE prevalence and to characterize ESBL genes in Burkina Faso. During 2 months (June-July 2014), 1602 clinical samples were sent for bacteriologic investigations to the microbiology laboratories of the tree main hospitals of Burkina Faso. Isolates were identified by mass spectrometry using a matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) BioTyper. Antibiotic susceptibility was tested using the disk diffusion method on Müller-Hinton agar. The different ESBL genes in potential ESBL-producing isolates were detected by PCR and double stranded DNA sequencing. Escherichia coli phylogenetic groups were determined using a PCR-based method. ESBL-PE frequency was 58 % (179 strains among the 308 Enterobacteriaceae isolates identified in the collected samples; 45 % in outpatients and 70 % in hospitalized patients). The CTX-M-1 group was dominant (94 %, CTX-M-15 enzyme), followed by the CTX-M-9 group (4 %). ESBL producers were more often found in E. coli (67.5 %) and Klebsiella pneumoniae (26 %) isolates. E. coli isolates (n = 202; 60 % of all Enterobacteriaceae samples) were distributed in eight phylogenetic groups (A = 49, B1 = 15, B2 = 43, C = 22, Clade I = 7, D = 37, F = 13 and 16 unknown); 22 strains belonged to the sequence type ST131. No association between a specific strain and ESBL production was detected. This report shows the alarming spread of ESBL genes in Burkina Faso. Public health efforts should focus on education (population and healthcare professionals), surveillance and promotion of correct and restricted antibiotic use to limit their dissemination.